Draft Annual Plan 1989-90 Guide Lines Uttar Pradesh - Planning Commission (Planning Commission, 1988)
The project envisages construction of a 716 M. long barrage on river Ghaghra at Katerniaghat about 10 km. below Indo-Nepal border and another barrage 408 M long on river Sarda both linked by a link canal. the available discharge of river Ghaghra and Sharda will be conveyed through a feeder canal to different branches of Sarda Canal system for intensifying irrigation thereon and taking up new areas. the project estimated to cost Rs.73,323 lakh will provide irrigation benefits to about 15.82 lakh hectares in Allahabad, Varanasi, Kheri, Sitapur, Lucknow, Bara Banki, Ghazipur, Rae Bareli, Sultanpur, Jaunpur, Azamgarh, Pratapgarh, Farrukhabad and Ballia Districts.
Government of Uttar Pradesh, Planning Department